2012
DOI: 10.3390/rs4041090
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time Method to Detect and Track Moving Objects (DATMO) from Unmanned Aerial Vehicles (UAVs) Using a Single Camera

Abstract: We develop a real-time method to detect and track moving objects (DATMO) from unmanned aerial vehicles (UAVs) using a single camera. To address the challenging characteristics of these vehicles, such as continuous unrestricted pose variation and low-frequency vibrations, new approaches must be developed. The main concept proposed in this work is to create an artificial optical flow field by estimating the camera motion between two subsequent video frames. The core of the methodology consists of comparing this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 31 publications
0
67
0
1
Order By: Relevance
“…We let YOLOv2 train on a diverse dataset composed of 282 training images that include the NFPA pictogram. The exact method we used to train YOLOv2 falls out of the scope of this paper, we do however provide an online article explaining the steps in detail 3 . Our training set contains a combination of real world photos (sourced using both online image search and our own drone flights) and images generated using the Unreal Editor, a software suite targeted at the development of games, simulations and visualizations.…”
Section: A Yolov2 Real-time Object Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We let YOLOv2 train on a diverse dataset composed of 282 training images that include the NFPA pictogram. The exact method we used to train YOLOv2 falls out of the scope of this paper, we do however provide an online article explaining the steps in detail 3 . Our training set contains a combination of real world photos (sourced using both online image search and our own drone flights) and images generated using the Unreal Editor, a software suite targeted at the development of games, simulations and visualizations.…”
Section: A Yolov2 Real-time Object Detectionmentioning
confidence: 99%
“…Other approaches focus on detecting and tracking moving objects in UAV imagery [3] [4]. These methods detect and track objects from an aerial platform using the onboard camera.…”
Section: Introductionmentioning
confidence: 99%
“…A well reconstructed 3-D image can be developed for city planning [43,44], environmental monitoring [45], Digital Surface Model (DSM) generation [46], disaster relief [47], surveillance and reconnaissance [48], etc.…”
Section: -D Distributed Scene Heterogeneous Parallel Simulationmentioning
confidence: 99%
“…Prior work demonstrating visual-based tracking has shown the potential of solely visual based tracking [16] (this algorithm operates on a restricted number of pixels from a frame at 10fps) and pose estimation [17] (designed to operate at 15fps). Related visual based UAV cueing has shown that visual odometry has been achieved at 25fps on a two-camera setup with a 1.5GHz Core 2 Duo processor [18].…”
Section: Introductionmentioning
confidence: 99%